ENVIRONMENTAL REVIEWS AND CASE STUDIES: Bringing Unmanned Aerial Systems Closer to the Environment. (22nd September 2015) - Detweiler, Carrick; Ore, John-Paul; Anthony, David; Elbaum, Sebastian; Burgin, Amy; Lorenz, Aaron
<x content-type="archive" xml:space="preserve">Abstract</x> Increasingly, Unmanned Aerial Systems (UASs) are changing the way that scientists and practitioners collect environmental data. Current UASs, however, are largely relegated to collecting data while flying remotely, far away in the air. This article examines two case studies where micro-UASs fly in immediate proximity to the environment, enabling them to collect physical samples and capture sensor data that cannot be obtained at a distance. The first case study presents an aerial water sampler that flies to remote locations and dips a pump into the water to collect samples for lab analysis. The second case study examines a UAS that flies within a meter of crops to accurately measure their height. Each requires different sensors and methods specifically tailored to operating and interacting near the environment. This article evaluates the performance of these systems and also presents preliminary validation that they collect datasets that are compatible with those gathered by existing approaches. Futhermore, it distills some common underlying design and operating principles shared by UASs aimed at working close to the environment. Finally, this article concludes that in spite of numerous pending challenges, UASs that directly interact with the environment will transform the way environmental data is collected. Environmental Practice 17: 188–200 (2015)